Case of non‐mosaic trisomy 20 in amniotic fluid cultures without anomalies in the fetus: Cytogenetic discrepancy between amniocytes and fetal blood. Issue 1 (28th August 2014) - Maeda, Kazuhisa; Imoto, Issei; Kaji, Takashi; Yoshida, Yukiko; Nakayama, Soichiro; Irahara, Minoru
Abstract We report a case of non‐mosaic trisomy 20 detected prenatally by amniocentesis during the 16th week of pregnancy. Fetal blood sampling showed a normal karyotype and no fetal, neonatal or infant abnormalities were observed. Amniotic fluid cell karyotyping revealed a trisomy 20 (47, XY, +20) with 100% trisomic cells (38/38); however, a subsequent cordocentesis revealed a normal male karyotype. Moreover, a follow‐up ultrasonographic examination did not reveal any major congenital malformations, and a healthy male infant was delivered subsequently at an appropriate gestational age without obvious anomalies. Cytogenetic analysis of blood lymphocytes from the infant revealed a normal karyotype, but cultured cells from the term placenta showed a mosaic karyotype 47, XY, +20/46, XY with 88% trisomic cells (44 of 50). Furthermore, no anomalies or developmental delays were observed in the neonatal period, thus suggesting two possibilities: confined placental mosaicism with the presence of normal and abnormal cell lineages, or generalized mosaicism affecting a limited number of tissues in both the placenta and fetus.